Clostridium Perfringens in Gas Gangrene: Still a Smoked Gun! - Preseau, Thierry (J Transl Int Med, 2020)
Gas gangrene (GG) remains a life-threatening and deadly disease. Early recognition together with daily surgical debridement remains the mainstay of therapy. We sought to describe a fatal case of necrotizing soft tissue infection, which was a gas gagrene in this case. This case was remarkable as two main sites were infected simultaneously in geographical zones very far from each other making dissemination between both sites almost impossible. The other particularity was the fact that the infection was caused at the same time by four different bacteria that is atypical in GG similar to that in streptoccocal necrotizing fasciitis where one bacteria is the causative agent (Clostridium perfringens for GG and group A streptococcus for necrotizing fasciitis).